Key concepts in crime and society - Coomber, Ross (SAGE key concepts, 2014)
Key Concepts in Crime and Society offers an authoritative introduction to key issues in the area of crime as it connects to society. By providing critical insight into the key issues within each concept as well as highlighted cross-references to other key concepts, students will be helped to grasp a clear understanding of each of the topics covered and how they relate to broader areas of crime and criminality. The book is divided into three parts: Understanding Crime and Criminality: introduces topics such as the social construction of crime and deviance, social control, the fear of crime, poverty and exclusion, white collar crime, victims of crime, race/gender and crime. Types of Crime and Criminality: explores examples including human trafficking, sex work, drug crime, environmental crime, cyber crime, war crime, terrorism, and interpersonal violence. Responses to Crime: looks at areas such as crime and the media, policing, moral panics, deterrence, prisons and rehabilitation